Proceedings of the 4th International Conference on Higher Education Advances (HEAd'18) 2018
DOI: 10.4995/head18.2018.8213
|View full text |Cite
|
Sign up to set email alerts
|

International academic mobility: the attraction factors of Brazilians students in Spain

Abstract: The mobility of university students abroad is a phenomenon of great importance

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 2 publications
0
2
0
1
Order By: Relevance
“…The survey design was based on a previous exploratory study in which the factors to be considered were identified (Kingeski & Olivella Nadal, 2018). The authors opted for qualitative information gathering techniques in the first stage of this work, with individual in-depth interviews with 28 Brazilian students in Spain.…”
Section: Methodsmentioning
confidence: 99%
“…The survey design was based on a previous exploratory study in which the factors to be considered were identified (Kingeski & Olivella Nadal, 2018). The authors opted for qualitative information gathering techniques in the first stage of this work, with individual in-depth interviews with 28 Brazilian students in Spain.…”
Section: Methodsmentioning
confidence: 99%
“…These situations, which are part of international students' decision-making factors, can occur in different geographies. In this framework, cultural compatibility (Ahmad & Buchanan, 2016), which is defined as the similarity between the host country and the culture of origin, can be distinctive (Ward & Kennedy, 1999;Kondakçı, 2011;Özoğlu et al, 2015;Kingeski & Olivella, 2018). Moreover, the experience of another country's culture and the attractiveness of international education are other cultural factors (Pawar et al, 2020;Cao et al, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…La primera etapa tuvo carácter cualitativo (entrevistas en profundidad) con 28 estudiantes brasileños que realizaran cursos superiores en España. Los resultados fueran presentados en la 4ª Conference on Advances in Higher Education -HEAd'18 (Kingeski & Olivella Nadal, 2018). Enseguida, se realizó una segunda etapa, Braz.…”
Section: Metodologíaunclassified